DESKRIPSI KEMAMPUAN PESERTA DIDIK MENYELESAIKAN SOAL HOTS MATERI HUKUM DASAR KIMIA SMA NEGERI PONTIANAK - Dina Cindiana; Hairida Hairida; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractQuestions on High Level Thinking Skills (HOTS) in class XI Science of Pontianak State High School and factors that enhance students' ability to answer HOTS questions. The research method used is descriptive research with a qualitative form of research. The study was conducted in three schools in Pontianak, namely MAN 1 Pontianak with a total sample of 20 people, SMA Negeri 8 Pontianak with a sample of 20 people and SMA Negeri 2 Pontianak with a total sample of 15 people with a total sample of 55 students. The instrument used was a HOTS problem with cognitive levels analyzing (C4) and analyzing (C5). The instrument used in this study has excellent validation results with an average percentage of small scale of 95.41% with a very high category and an average percentage of large scale of 93.75% with a very high category. The research results obtained are the participation of students in solving HOTS questions in a total of 19.90% with a very low category. The percentage of students' abilities in the analysis aspect (C4) was 23.76% and in the evaluation aspect (C5) was 24.95%. The conclusion obtained is that students are still unable to understand the basic concepts of complete chemical law.Keywords: About HOTS, Basic Laws of Chemistry, Description,